2012
DOI: 10.1080/07370024.2012.656050
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Aiding Autobiographical Memory Using the SenseCam

Abstract: Human memory is a dynamic system which makes accessible certain memories of events based on a hierarchy of information, arguably driven by personal significance. Not all events are remembered, but those that are tend to be more psychologically relevant. In contrast, lifelogging is the process of automatically recording aspects of one"s life in digital form without loss of information. In this article we share our experiences in designing computer-based solutions to assist people review their visual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(6 citation statements)
references
References 52 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Images promote more detail-rich recall compared to other types of data [18,30] as they contain rich contextual information [32]. Thus, pictorial lifelogs were extensively researched as a means to augment human memory (e.g., [4,14,21,33,48,49]). Pictorial lifelogs could come from wearable cameras capturing first-person perspective excluding the lifelogger or from infrastructure cameras capturing a third-person perspective including the lifelogger.…”
Section: Lifelogs As Memory Prosthesesmentioning
confidence: 99%
“…Images promote more detail-rich recall compared to other types of data [18,30] as they contain rich contextual information [32]. Thus, pictorial lifelogs were extensively researched as a means to augment human memory (e.g., [4,14,21,33,48,49]). Pictorial lifelogs could come from wearable cameras capturing first-person perspective excluding the lifelogger or from infrastructure cameras capturing a third-person perspective including the lifelogger.…”
Section: Lifelogs As Memory Prosthesesmentioning
confidence: 99%
“…Much of the research on lifelogging has focused on the use of wearable cameras to support remembering in people with memory disorders (for review, see Silva, Pinho, Macedo, & Moulin, 2018). Several studies report improvements in how many events or details participants, healthy or otherwise, remember after reviewing photos taken from an automaticcapture camera (e.g., Crete-Nishihata et al, 2012;Doherty et al, 2012;Finley et al, 2011;Kalnikaite, Sellen, Whittaker, & Kirk, 2010;Lee & Dey, 2008;Sas et al, 2013;Sellen et al, 2007;Woodberry et al, 2015). Beyond improving recall, some studies have reported that reviewing photos taken with an automatic-capture camera can enhance subjective measures of recollection like feelings of vividness (St. Jacques, Conway, & Cabeza, 2011) and memory specificity (Silva, Pinho, Macedo, & Moulin, 2013).…”
Section: The Consequences Of Photographic Reviewmentioning
confidence: 99%
“…Collective memory is a continuous trend of thought and a kind of non-human continuity, because it only retains what is active and can survive in the collective ritual from the past. Studies have shown that vision has beneficial effects on individual memory [28][29][30]. Loveday and Conway [31] demonstrated that images are more effective at evoking memories than written records of personal experiences.…”
Section: Memory and Innovative Designmentioning
confidence: 99%